2019
DOI: 10.1002/anie.201909052
|View full text |Cite
|
Sign up to set email alerts
|

Diketopiperazine Formation in Fungi Requires Dedicated Cyclization and Thiolation Domains

Abstract: Cyclization of linear dipeptidyl precursors derived from nonribosomal peptide synthetases (NRPSs) into 2,5diketopiperazines (DKPs) is ac rucial step in the biosynthesis of alarge number of bioactive natural products.However,the mechanism of DKP formation in fungi has remained unclear, despite extensive studies of their biosyntheses.H ere we show that DKP formation en route to the fungal virulence factor gliotoxin requires as eemingly extraneous couplet of condensation (C) and thiolation (T) domains in the NRPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…41 Analysis of the active sites of ThmB-C T and TqaA-C T domains showed that the ThmB-C T domain contains the intact characteristic "HHxxxD" motif of the classical C domain (Figure S6); however, the first His residue is mutated to a Ser residue in the TqaA-C T domain (SHxxxD). 40 Further phylogenetic analysis among fungal hrPKS−C T domains, single-and multimodule NRPS-C T domain, 40,42 diketopiperazine NRPS (e.g., GliP)-C T domain, 43 classical NRPS C domains, as well as ester bond-forming C domains from bacteria 43 showed that the ThmB-C T domain was clustered in a separate clade, implying that it has a new catalytic function (Figure 4A and Figure S6A).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…41 Analysis of the active sites of ThmB-C T and TqaA-C T domains showed that the ThmB-C T domain contains the intact characteristic "HHxxxD" motif of the classical C domain (Figure S6); however, the first His residue is mutated to a Ser residue in the TqaA-C T domain (SHxxxD). 40 Further phylogenetic analysis among fungal hrPKS−C T domains, single-and multimodule NRPS-C T domain, 40,42 diketopiperazine NRPS (e.g., GliP)-C T domain, 43 classical NRPS C domains, as well as ester bond-forming C domains from bacteria 43 showed that the ThmB-C T domain was clustered in a separate clade, implying that it has a new catalytic function (Figure 4A and Figure S6A).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…230 The same Cterminal C T -PCP arrangement is found in other NRPSs, including the previously mentioned nanangelenin B synthase NanA, suggesting a conserved function. 182,230 Fig. 27 Structure of a C T domain.…”
Section: Chain Release Catalysed By Aldoketo Reductasesmentioning
confidence: 54%
“…230 Interestingly, the PCP downstream of the GliA C T domain is also essential for chain release, indicating that it serves to tether the NRP intermediate specically for the C T domain. 230 The same Cterminal C T -PCP arrangement is found in other NRPSs, including the previously mentioned nanangelenin B synthase NanA, suggesting a conserved function. 182,230 Fig.…”
Section: Chain Release Catalysed By Aldoketo Reductasesmentioning
confidence: 99%
“…Diketopiperazines are expected to be biosynthetically assembled from two amino acid building blocks by nonribosomal peptide synthetases [ 65 ]. On the other hand, the biogenesis of many sulfur-containing compounds remains incompletely understood.…”
Section: Prospectsmentioning
confidence: 99%